Terminal lipophilization of a unique DNA dodecamer by various nucleolipid headgroups: Their incorporation into artificial lipid bilayers and hydrodynamic properties - Werz, Emma; Rosemeyer, Helmut (Beilstein Journal of Organic Chemistry, 2015)
A series of six cyanine-5-labeled oligonucleotides (LONs 10–15), each terminally lipophilized with different nucleolipid head groups, were synthesized using the recently prepared phosphoramidites 4b–9b. The insertion of the LONs within an artificial lipid bilayer, composed of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE), was studied by single molecule fluorescence spectroscopy and microscopy with the help of an optically transparent microfluidic sample carrier with perfusion capabilities. The incorporation of the lipo-oligonucleotides into the bilayer was studied with respect to efficiency (maximal bilayer brightness) as well as stability against perfusion (final stable bilayer brightness). Attempts to correlate these parameters with the log P values of the corresponding nucleolipid head groups failed, a result which clearly demonstrates that not only the lipophilicity but mainly the chemical structure and topology of the head group is of decisive importance for the optimal interaction of a lipo-oligonucleotide with an artificial lipid bilayer. Moreover, fluorescence half-live and diffusion time values were measured to determine the diffusion coefficients of the lipo-oligonucleotides.
Keywords: lipid bilayer; lipo-oligonucleotides; nucleic acids; nucleolipids